2016
DOI: 10.1007/s00027-016-0514-z
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of aquatic plant and microfaunal seed and egg bank communities within a forested floodplain system of a temperate Australian river

Abstract: Aquatic plant and microfaunal propagule banks represent a major source of regenerative potential in riverfloodplain ecosystems. This study investigated the spatial patterns of microfaunal and aquatic plant propagule bank communities within a wetland complex on the forested floodplain of a temperate Australian river system that had recently been completely inundated and dried again. Microfaunal emergence and aquatic plant germination were examined at the wetland complex spatial scale by incubating sediment samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…In relation to the drivers of alpha and beta diversity, substrate heterogeneity significantly accounted for alpha diversity. Earlier studies described significant variation in the hatchling community associated with fine‐scale differences in the sediment conditions within a given waterbody (Nielsen, Jasper, Ning, & Lawler, 2015; Portinho, Nielsen, Ning, Paul, & Nogueira, 2017; Santangelo, de Esteves, Manca, & Bozelli, 2011). This pattern could likely reflect a differential deposition of the egg bank within each pond (Gyllström & Hansson, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the drivers of alpha and beta diversity, substrate heterogeneity significantly accounted for alpha diversity. Earlier studies described significant variation in the hatchling community associated with fine‐scale differences in the sediment conditions within a given waterbody (Nielsen, Jasper, Ning, & Lawler, 2015; Portinho, Nielsen, Ning, Paul, & Nogueira, 2017; Santangelo, de Esteves, Manca, & Bozelli, 2011). This pattern could likely reflect a differential deposition of the egg bank within each pond (Gyllström & Hansson, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A detailed limnological and biota description of the four lakes can be found in Granado and Henry (2008) and Panarelli et al (2008). From each lake, sediment samples were collected on 31st January 2017 from seven equidistant sampling stations along a transect from lake shore (shallow area), stopping at pelagic zone (deep area) to sample the spatial heterogeneity of dormant eggs within the lakes (Portinho et al, 2016). At each sampling station, surface sediment samples (<10 cm depth) were collected by Van Veen grab (0.06 m 2 ) and placed in a plastic bag following the methods of Nielsen et al (2003Nielsen et al ( , 2007.…”
Section: Field Sites and Sediment Collection Containing Dormant Zooplmentioning
confidence: 99%
“…Although it is widely accepted that flood history is a driver of egg bank composition and hatching patterns (Cáceres & Tessier, 2003; Paidere, 2009; Portinho et al., 2017; Shiel et al., 1998; Vanoverbeke & De Meester, 2015), several important knowledge gaps remain with respect to the relative importance of these mechanisms and how they manifest as distinct spatial patterns in relation to flood history. For example, it has been demonstrated that sediments that have been flooded within the past 1–7 years tend to yield more abundant and diverse microcrustacean assemblages than sediments that have not been flooded for a decade or more (Boulton & Lloyd, 1992; Jenkins & Boulton, 2007; Nielsen et al., 2013).…”
Section: Introductionmentioning
confidence: 99%